Introduksi Neochetina eichhorniae (Coleoptera: Curculionidae) Potensi Dampak Non-Target Terhadap Komunitas Tumbuhan Lokal - Sapdi Sapdi (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
The Introduction of Neochetina eichhorniae (COLEOPTERA: CURCULIONIDAE): The Potency of Non-Target Impact on Local Plant CommunitiesABSTRACT. When introduce an exotic insect species as a biological agent thought cause non-target impacts, directly or indirectly, on local plants species. The objective of this research is to evaluate the potency of nontarget impacts of introducing Neochetina eichhorniae on local plants aquatic communities. The results of the research indicated that the weevil showed a high preference and host specific on waterhyacinth, and so far the house shifting was not occur. Insitu observation showed that this biological agent was not found in any others aquatic and non aquatic plants living around water areas. This data indicated that host range expansion by the weevil was not consist.